Illustration of bounded ambiguity. I, The 'feedback culture' of a management consultancy firm - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
This case study presents an assessment of a human resource management system in a large management consultancy firm. Despite flaws in the system, it is largely viewed as an identity resource and a factor of image management. There is an ambiguity between people's individual experiences of human resource management within the firm and the functions of the overall system.
Originally Published in: Alvesson, M. (2012). Illustration of Bounded Ambiguity I: The `Feedback Culture' of a Management Consultancy Firm. In Understanding organizational culture (2nd ed., pp. 148-149). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Personnel management -- Case studies; Corporate culture -- Case studies